Efficient quantum secure direct communication with complete Bell‐state measurement - Gao, Cheng‐Yan; Guo, Peng‐Liang; Ren, Bao‐Cang (Quantum engineering, 2021)
Quantum secure direct communication (QSDC) is a powerful technique of transmitting confidential information directly and securely based on the pre‐established secure quantum channel and block transmission. Here we propose an efficient QSDC protocol using the complete Bell‐state measurement (CBSM) resorting to linear optical elements and temporal‐polarization hyperentanglement. In this protocol, the polarized entangled photons are utilized as the information carrier, and all the detection events of CBSM can be identified with common single‐photon detectors instead of photon number resolving detectors due to the introduction of temporal degree of freedom (DOF). Moreover, since all the two‐photon detection events in CBSM are effective and can be preserved with the efficiency of 100% rather than 50% in the previous QSDC, the quantum efficiency of QSDC can be doubled by encoding more messages on entangled photon pairs.